UTILIZATION OF GEOTAGGED PHOTOGRAPH, REMOTE SENSING, AND GIS FOR POST-DISASTER DAMAGE ASSESSMENT - Sapta Nugraha; Michiel Damen (Faculty of Geography, Universitas Gadjah Mada, 2013)
Merapi eruption in 2010 causing major damage impact on that region. Post-disaster damage assessment thathas been done by the government have not been supported with a good spatial data so that validation isrelatively weak. Method of post-disaster damage assessment, particularly assessment of building damage usinggeotagged photos, remote sensing and GIS is expected to improve the method of damage assessment by thegovernment of Indonesia. Geojot Applications for Android Smartphone/Tablet allows the assessment of buildingdamage to be included in the photo attribute. Interpretation of satellite imagery of building damage is done byusing three indications: building visibility, building collapse, and building roof. Geotagged photograph cancomplement the needs of building damage assessment from satellite images because it can describe thestructural and non-structural damage to buildings clearly. Geotagged photograph with GPS Lock-Off moderequiring information on the direction and distance of the object being photographed. Geotagged photographwith the QR code is the most profitable because the identity of the building is already known and can bematched with an existing database.